Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1039/b108356b
|View full text |Cite
|
Sign up to set email alerts
|

TS-1 zeolite microengineered reactors for 1-pentene epoxidation

Abstract: A zeolite-based microengineered reactor was fabricated and tested for 1-pentene epoxidation over titanium silicalite-1 (TS-1) catalyst, which has been selectively incorporated within the microreactor channel using a new synthesis procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…In addition, new possibilities exist for the directed assembly and growth of complex and functional materials beyond films for separations, such as molecular sensors, mechanically stable dielectrics, and novel reaction-diffusion devices. [231][232][233][234] …”
Section: Discussionmentioning
confidence: 99%
“…In addition, new possibilities exist for the directed assembly and growth of complex and functional materials beyond films for separations, such as molecular sensors, mechanically stable dielectrics, and novel reaction-diffusion devices. [231][232][233][234] …”
Section: Discussionmentioning
confidence: 99%
“…Gavriilidis et al used hydrogen peroxide as an oxidant to facilitate epoxidation of 1-pentene in a microchannel coated with titanium silicalite-1 zeolite (TS-1, Scheme 27). 249,250 Reaction rates increased with increasing amounts of Ti in the zeolite framework. It was also observed that the crystal size largely affected the reaction rate.…”
Section: Oxidation Processes In Flow By Means Of Hydrogen Peroxidementioning
confidence: 99%
“…Epoxidation of 1-pentene with H2O2 in a TS-1 immobilized microreactor. 249 Epoxidized soybean oil (ESO) is an important chemical intermediate, which can be used as plasticizer in polyvinyl chloride plastics and stabilizer for plastics. 251 Kinetic modelling of soybean oil epoxidation at elevated temperatures in a microreactor demonstrated that this would lead to much shorter reaction times.…”
Section: Oxidation Processes In Flow By Means Of Hydrogen Peroxidementioning
confidence: 99%
“…[16] Obviously, the availability of highly oriented TS-1 films, especially along the b-axis, will trigger their application in innovative materials, microreactors, and even microelectronic devices. [17][18][19] TS-1 zeolite has the same tetrahedral framework as Al-ZSM-5 and silicalite-1 MFI zeolites. However, the introduction of Ti atoms into the framework requires a substantially longer hydrothermal reaction time.…”
mentioning
confidence: 99%